Diagnostic laparoscopy should be performed before definitive resection for pancreatic cancer: a financial argument. Issue 2 (15th August 2014) - Jayakrishnan, Thejus T.; Nadeem, Hasan; Groeschl, Ryan T.; George, Ben; Thomas, James P.; Ritch, Paul S.; Christians, Kathleen K.; Tsai, Susan; Evans, Douglas B.; Pappas, Sam G.; Gamblin, T. Clark; Turaga, Kiran K.
Abstract Objectives Laparoscopy is recommended to detect radiographically occult metastases in patients with pancreatic cancer before curative resection. This study was conducted to test the hypothesis that diagnostic laparoscopy (DL) is cost‐effective in patients undergoing curative resection with or without neoadjuvant therapy (NAT). Methods Decision tree modelling compared routine DL with exploratory laparotomy (ExLap) at the time of curative resection in resectable cancer treated with surgery first, (SF) and borderline resectable cancer treated with NAT. Costs (US$) from the payer's perspective, quality‐adjusted life months (QALMs) and incremental cost‐effectiveness ratios (ICERs) were calculated. Base case estimates and multi‐way sensitivity analyses were performed. Willingness to pay (WtP) was US$4166/QALM (or US$50 000/quality‐adjusted life year). Results Base case costs were US$34 921 for ExLap and US$33 442 for DL in SF patients, and US$39 633 for ExLap and US$39 713 for DL in NAT patients. Routine DL is the dominant (preferred) strategy in both treatment types: it allows for cost reductions of US$10 695/QALM in SF and US$4158/QALM in NAT patients. Conclusions The present analysis supports the cost‐effectiveness of routine DL before curative resection in pancreatic cancer patients treated with either SF or NAT.